A new multi‐messenger description of starburst galaxies emission: perspectives for neutrino and gamma‐ray observations. Issue 1 (26th January 2023) - Marinelli, Antonio; Ambrosone, Antonio; Chianese, Marco; Fiorillo, Damiano; Miele, Gennaro; Pisanti, Ofelia
Abstract: Star‐forming and starburst galaxies (SBGs), which are well‐known cosmic‐ray (CR) reservoirs, are expected to emit gamma rays and neutrinos predominantly via hadronic collisions. In this work we analyze the 10‐year Fermi‐Low Energy Technique (LAT) spectral energy distributions of 13 nearby galaxies by means of a physical model that accounts for high‐energy proton transport in starburst nuclei and includes the contribution of primary and secondary electrons. In particular, we test the hypothesis that the observed gamma‐ray fluxes are mostly due to star‐forming activity, which is in agreement with the available star formation rates coming from infrared (IR) and ultraviolet (UV) observations. Through this observation‐based approach, we determine the most‐likely neutrino counterparts from star‐forming and SBGs and quantitatively assess the ability of current and upcoming neutrino telescopes to detect them as point‐like sources. We also generate mock gamma‐ray data to simulate the Cherenkov Telescope Array (CTA) performance in detecting these sources. Moreover, we propose a test to discriminate between the two different CR transport models for the starburst nuclei by looking at the different gamma‐ray expectations. We point out that current data already gives a slight preference to CR models, which are dominated by advection.